Economic implications of incorporating emission controls to mitigate air pollutants emitted from a modeled hydrocarbon‐fuel biorefinery in the United States. (15th July 2016) - Bhatt, Arpit; Zhang, Yimin; Davis, Ryan; Eberle, Annika; Heath, Garvin
Abstract: The implementation of the US Renewable Fuel Standard is expected to increase the construction and operation of new biofuel facilities. Allowing this industry to grow without adversely affecting air quality is an important sustainability goal sought by multiple stakeholders. However, little is known about how the emission controls potentially required to comply with air quality regulations might impact biorefinery cost and deployment strategies such as siting and sizing. In this study, we use a baseline design for a lignocellulosic hydrocarbon biofuel production process to assess how the integration of emission controls impacts the minimum fuel selling price (MFSP) of the biofuel produced. We evaluate the change in MFSP for two cases as compared to the baseline design by incorporating (i) emission controls that ensure compliance with applicable federal air regulations and (ii) advanced control options that could be used to achieve potential best available control technology (BACT) emission limits. Our results indicate that compliance with federal air regulations can be achieved with minimal impact on biofuel cost ( 0.02 per gasoline gallon equivalent (GGE) higher than the baseline price of 5.10 GGE −1 ). However, if air emissions must be further reduced to meet potential BACT emission limits, the cost could increase nontrivially. For example, the MFSP could increase to 5.50 GGE −1 by adopting advanced emission controls to meet potential boiler BACT limits. Given tradeoffs among emission control costs, permitting requirements, and economies of scale, these results could help inform decisions about biorefinery siting and sizing and mitigate risks associated with air permitting. Published 2016. This article is a U.S. Government work and is in the public domain in the USA. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.